2014
DOI: 10.1002/ana.24257
|View full text |Cite
|
Sign up to set email alerts
|

Dying neurons in thalamus of asphyxiated term newborns and rats are autophagic

Abstract: These results show for the first time that autophagy is enhanced in severe HIE in dying thalamic neurons of human newborns, as in rats. Experimental neuroprotective strategies targeting autophagy could thus be a promising lead to follow for the development of future therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 58 publications
2
55
0
Order By: Relevance
“…ADC values were lower in the thalamus than in the basal ganglia, and were increased in both areas during the first week after birth. It has been shown that restricted diffusion corresponds to cytotoxic edema and therefore irreversible lesions with neuronal cell death [19].…”
Section: Discussionmentioning
confidence: 99%
“…ADC values were lower in the thalamus than in the basal ganglia, and were increased in both areas during the first week after birth. It has been shown that restricted diffusion corresponds to cytotoxic edema and therefore irreversible lesions with neuronal cell death [19].…”
Section: Discussionmentioning
confidence: 99%
“…23, 24 Selective KO of Atg7 in neuronally committed cells shows that basal levels of autophagy are required for normal neuron survival, 16, 25 and autophagy is a protective mechanism in response to numerous stresses. 26, 27 Overactivated autophagy induces autophagic cell death, 28 and genetic inhibition of autophagy prevents hypoxia–ischemia-induced neuronal cell death in multiple brain regions. 18 Autophagy has also been shown to be involved in irradiation-induced cell death in cancer cells, 29, 30 and autophagy inhibitors can enhance radiosensitivity in gliomas; 31 however, it is still unknown if inhibition of autophagy works to prevent irradiation-induced neural stem and progenitor cell death in the juvenile brain.…”
Section: Discussionmentioning
confidence: 99%
“…Later, in both rat and mouse models of perinatal HI, ultrastructural studies revealed numerous autophagosomes and autolysosomes in the cytosol of dying neurons (Ginet et al, 2009; Koike et al, 2008; Zhu et al, 2005). In P7 hypoxic‐ischemic rat pups, our group showed that an LC3‐II increase was already detectable as soon as 6 h after the insult and peaked at around 24 h (Ginet et al, 2014a; Ginet et al, 2009). Autophagic flux enhancement was suggested by an increase in both LC3‐positive dots and lysosomal markers (LAMP1, cathepsins) and activity (acid phosphatase, β‐hexosaminidase) that can occur in the same dying neurons (Ginet et al, 2009).…”
Section: Autophagy Mediated Cell Death In Neonatal Himentioning
confidence: 94%
“…Few studies have addressed the functional role of enhanced autophagy in neonatal cerebral HI models until now. All the studies suggest that enhanced autophagy plays a role in the apoptotic pathway since dying neurons can express both autophagic and apoptotic features (Carloni et al, 2008; Ginet et al, 2014a; Ginet et al, 2009; Koike et al, 2008) and since autophagy inhibition decreases apoptotic markers such as caspase‐3 activation (Carloni et al, 2008; Koike et al, 2008). Interestingly, we showed that autophagy could mediate apoptosis in primary cortical neurons cultures treated with classical apoptotic stimuli (Grishchuk et al, 2011).…”
Section: Autophagy Mediated Cell Death In Neonatal Himentioning
confidence: 99%